Life cycle analysis on sequential recovery of copper and gold from waste printed circuit boards - Rao M.D.; Meshram R.B.; Singh K.K.; Morrison C.A.; Love J.B. (My University, 2025)
Informal recycling activities of waste printed circuit boards, such as pyrolysis and landfilling, cause severe environmental harm to society. Pyrolysis of resin and polymer fraction leads to the generation of toxic effluents, and landfilling causes the leaching of heavy metals into the groundwater. A sustainable and eco-friendly way to recover base and precious elements will be an economically attractive option. Current research studied the cradle-to-gate environmental impacts of the sequential recovery of copper and gold through delamination, leaching, solvent extraction, electrowinning and cementation from waste printed circuit boards with the help of life cycle assessment. GaBi software was utilized to assess environmental impacts such as global warming, abiotic depletion (fossil), acidification potential and human toxicity potential during the process. Inventory data was collected by conducting several experiments and from optimizing parameters for recycling and separating 4.53 g of copper and 2.25 mg of gold from 16 g of component-free waste printed circuit boards. Results indicate that the chemical pre-treatment or delamination process for separating metal clads from the non-metallic fraction is primarily involved in the impact category. The higher impact during delamination is due to electricity consumption. The proposed study also corroborates the industrial viability of recycling valuable metals from waste printed circuit boards to minimize the environmental impacts. The outcomes of this work could be beneficial in creating the environmental guiding principle for WPCBs recycling plants. © 2023 Elsevier Ltd